Cajaninstilbene Acid Ameliorates Cognitive Impairment Induced by Intrahippocampal Injection of Amyloid-β1–42 Oligomers - Wang, Li-Sha; Tao, Xue; Liu, Xin-Min; Zhou, Yun-Feng; Zhang, Meng-Di; Liao, Yong-Hong; Pan, Rui-Le; Chang, Qi (Frontiers in Pharmacology, 2019)
Amyloid-β1-42 (Aβ1-42) oligomers play an important role at the early stage of Alzheimer’s disease (AD) and have been a vital target in the development of therapeutic drugs for AD. Cajaninstilbene acid (CSA), a major bioactive stilbene isolated from pigeon pea (Cajanus cajan) leaves, exerted the neuroprotective property in our previous studies. The present study utilized a validated mouse model of early-stage AD induced by bilateral injection of Aβ1-42 oligomers into hippocampal CA1 regions (100 pmol/mouse) to investigate the cognitive enhancing effects of CSA and the underlying mechanism, by a combination of animal behavioral tests, immunohistochemistry, liquid chromatography-tandem mass spectrometry analysis, and Western blot methods. Intragastric administration of CSA (7.5, 15 and 30 mg/kg) attenuated the impairment of learning and memory induced by Aβ1-42 oligomers. CSA stimulated Aβ clearance and prevented microglial activation and astrocyte reactivity in the hippocampus of model mice. It also decreased the high levels of Glu but increased the low levels of GABA. In addition, CSA inhibited excessive expression of GluN2B-containing NMDARs and upregulated the downstream PKA/CREB/BDNF/TrkB signaling pathway. These results suggest that CSA could be a potential therapeutic agent at the early stage of AD.